Association of Insulin Resistance Indexes to Carotid Intima–Media Thickness - Sciacqua, Angela; Marini, Maria Adelaide; Hribal, Marta Letizia; Perticone, Francesco; Sesti, Giorgio (PloS one, 2013)
Accumulating evidence suggests an association between insulin resistance (IR) and cardiovascular diseases The aim of this study was to examine the relationship between indexes of IR and common carotid intima-media thickness (IMT), an indicator of vascular damage. In 847 non-diabetic Caucasians a 75 g oral glucose tolerance test was performed and surrogate indexes of IR were computed according to published formulas. IMT was measured by ultrasound method. The Stumvoll ISI(OGTT) index was correlated with IMT more strongly than the other indexes of IR. The IR indexes correlated significantly (P<0.0001) with all cardiovascular risk factors examined. The Stumvoll ISI(OGTT) index was correlated with waist circumference and high sensitivity C-reactive protein more strongly than the other indexes of IR. The area under the ROC curve (AUC), used to evaluate the accuracy of the IR indexes in identifying individuals with vascular damage defined as IMT >0.9 mm, for the Stumvoll ISI(OGTT) index was significantly higher (0.710) as compared with the AUCs of Matsuda (0.642) (P = 0.0009), OGIS (0.666) (P = 0.04), HOMA (0.611) (P<0.0001) and Liver IR (0.648) (P = 0.0008) indexes. In a logistic regression model adjusted for age and gender, subjects in the lowest tertile of the Stumvoll ISI(OGTT) index had the highest risk of having vascular damage (OR 4.95, 95% CI 2.99-8.192) as compared to the corresponding tertiles of the other surrogate indexes. The Stumvoll ISI(OGTT) index correlated more strongly than other validated surrogates indexes of IR with carotid IMT, and, therefore, it might be a significant indicator of vascular damage.